(untitled) (World Science, 2020)
The article discusses essential problems of discursive essay writing method during professional formation of a future teacher, conceptual approaches and technique of step-by-step preparation for its writing, as well as approaches to assessing and analyzing the level of performance using defined set of criteria given specifics of social and pedagogical problems. General theoretical bases of interpretation of discourse features and logic and technological support of its implementation are described, given the specifics of essay writing method, which was not relevant in the system of information and reproductive professional education.